Understanding the Accuracy and Best Use of the Woodland Stick as a Tree Height and Diameter Measurement Tool: a Case Study in Oregon - Belart, Francisca; Grand, Lauren; Christiansen, Alicia (Journal of extension, 2025)
We conducted a study to assess the accuracy of the Woodland Stick in determining tree diameter and height as compared to professional measurements and how bias can affect tree volume calculation. After comparing professional measurements with five non-professionals (NP’s) using the Woodland Stick, we found that three out of five NP’s had significant differences in mean dbh, and all of the NP’s had significant differences in mean total height. The overall bias for dbh across users was +0.5 inches and +5.1 ft for height. These deviations can result in volume differences between 0 and 30 bf on a single tree.